2016
DOI: 10.1111/ggi.12911
|View full text |Cite
|
Sign up to set email alerts
|

Japanese‐language Dementia Knowledge Assessment Scale: Psychometric performance, and health student and professional understanding

Abstract: The DKAS-J provides a useful tool for conceptualizing baseline knowledge, changes in understanding and knowledge deficits. Such a measure will prove valuable for the design and development of educational interventions as dementia increases in Japan and worldwide. Geriatr Gerontol Int 2017; 17: 1746-1751.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
35
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 18 publications
11
35
2
1
Order By: Relevance
“…CFA were performed using model structures proposed by previous studies (Annear, Otani, et al, 2017;Annear, Toye, et al, 2017;Annear et al, 2015). A model is considered good if (1) the comparative fit index (CFI) >0.95; (2) the Tucker-Lewis index (TLI) >0.95 and (3) the root mean square error of approximation (RMSEA) <0.06 (Hu & Bentler, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CFA were performed using model structures proposed by previous studies (Annear, Otani, et al, 2017;Annear, Toye, et al, 2017;Annear et al, 2015). A model is considered good if (1) the comparative fit index (CFI) >0.95; (2) the Tucker-Lewis index (TLI) >0.95 and (3) the root mean square error of approximation (RMSEA) <0.06 (Hu & Bentler, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…A confirmatory factor analysis (CFA) amongst an international cohort of volunteer respondents (from nine different countries) who had participated in a dementia-related online course indicated a 4-factor structure for the DKAS, with the number of items being reduced to 25 (Annear, Toye, et al, 2017). To our knowledge, with the exception of Japan (Annear, Otani, & Li, 2017), the DKAS has not been validated in any other country outside of Australia. However, a principal component analysis revealed that the Japanese translated version did not support the proposed 25 items 4-factor structure, but instead was more appropriate when used as an 18 items unidimensional scale (Annear, Otani, et al, 2017).…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…No studies that directly addressed the mental health or cognitive care education needs of the Japanese aged care workforce in the last 20 years were identified. A recent study conducted by the authors examined Japanese knowledge of dementia among a sample of 185 health students and educators as part of pilot testing for a dementia knowledge scale (Annear et al 2016c). This study revealed preliminary evidence for a low level of understanding about dementia and fundamental misconceptions concerning the clinical course of the syndrome, symptomatology and the efficacy of pharmacological interventions for behavioural symptoms (Annear et al 2016c).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study conducted by the authors examined Japanese knowledge of dementia among a sample of 185 health students and educators as part of pilot testing for a dementia knowledge scale (Annear et al 2016c). This study revealed preliminary evidence for a low level of understanding about dementia and fundamental misconceptions concerning the clinical course of the syndrome, symptomatology and the efficacy of pharmacological interventions for behavioural symptoms (Annear et al 2016c). Such results suggest that there is potential educational need among those who will comprise the dementia care workforce in the coming years in Japan.…”
Section: Introductionmentioning
confidence: 99%